Pemerolehan Bahasa dan Penggunaan Bahasa Anak Usia Sekolah Dasar - Tri Mahajani, Ruyatul Hilal Muhtar (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2018)
Abstract. The present study aims to examine a description of language acquisition and its usage by pupils in their daily conversations. This study employed a longitudinal case study and applieda descriptive method, while it used a content analysis for the research technique. The resultrevealed a finding upon the young learner language acquisition and its usage, the language acquisition included Bahasa Indonesia, Javanese language, Sundanese language and English language. The uses of language for a system, a personal expression, and an interpersonal expression were broad good enough and were uttered structurally, however, mistakes were founded on applying structures and making meaning to language in use. To pupils whom are at elementary school level, they have acquired a range of language structure and its use for perfection. Their parents, teachers, and their society have any real and valuableinfluence over them in the way language is structured and is used for exemplifying examples ofthe perfect language acquisition.